2017
DOI: 10.1515/sjph-2017-0027
|View full text |Cite
|
Sign up to set email alerts
|

Running injuries in the participants of Ljubljana Marathon

Abstract: IntroductionThe aim of our study was to determine the self-reported incidence and prevalence of running-related injuries among participants of the 18th Ljubljana Marathon, and to identify risk factors for their occurrence.MethodsA customized questionnaire was distributed over registration. Independent samples of t-test and chi-square test were used to calculate the differences in risk factors occurrence in the injured and non-injured group. Factors which appeared significantly more frequently in the injured gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 21 publications
5
23
1
1
Order By: Relevance
“…However, most of the research work has been done on able-bodied athletes and the identification of factors affecting injuries and/or traumas depending on the type of sport. Among other things, a significant effect of somatic features and body composition indicators predisposing to injuries and/or trauma has been emphasized [19][20][21][22][23][24]. Our results are consistent with these findings, as body mass significantly correlated with the prevalence of injuries among goalball players.…”
Section: Discussionsupporting
confidence: 91%
“…However, most of the research work has been done on able-bodied athletes and the identification of factors affecting injuries and/or traumas depending on the type of sport. Among other things, a significant effect of somatic features and body composition indicators predisposing to injuries and/or trauma has been emphasized [19][20][21][22][23][24]. Our results are consistent with these findings, as body mass significantly correlated with the prevalence of injuries among goalball players.…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, these results are not yet fully elucidated in the literature. Vitez et al 8 and Linton et al 7 observed that overweight runners are more susceptible to injuries than those with normal weight, corroborating our findings, which demonstrate an unclear significant correlation between BMI and VAS, Kujala and Lysholm scores.…”
Section: Discussionsupporting
confidence: 91%
“…Our results indicate that age has a trivial correlation with specific knee and pain questionnaires. On the contrary, Gionnogueron et al, 3 Van Gent et al, 2 and Vitez et al 8 pointed out that advanced age is a risk factor for lower limb injury. A Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations